PHYTOL DEGRADATION PRODUCTS AS BIOGEOCHEMICAL TRACERS IN AQUATIC ENVIRONMENTS - Rontani J.F.; Volkman J.K. (My University, 2003)
Phytol (the ester-linked side-chain of chlorophyll-a) is perhaps the most studied biomarker of those found in modern aquatic environments. This paper reviews recent studies of phytol degradation and provides an update on more classical studies. After a discussion of the biosynthesis and isotopic fractionation of phytol, we examine the different biotic and abiotic processes which may play a significant role during the diagenesis of this widely distributed isoprenoid alcohol: (i) photodegradation of the chlorophyll phytyl chain in senescent phytoplanktonic cells, (ii) hydroperoxide-induced oxidation of the chlorophyll phytyl chain in senescent phytoplanktonic cells, (iii) degradation of the chlorophyll phytyl chain during marine invertebrate feeding, (iv) aerobic and anaerobic biodegradation of phytol, (v) clay-catalysed degradative processes, and (vi) sulfur incorporation. Emphasis is given to the mechanisms of these processes and to the structures of the products formed. We conclude with some remarks on the potential and constraints of the main phytol degradation products as biogeochemical tracers and highlight some areas requiring further work.